A COMPARATIVE STUDY OF EXTERNAL VERSUS ENDOSCOPIC DACRYOCYSTORHINOSTOMY - Dr. Shekhar Srivastava; Dr. C.M Kohli; Dr. Avaneesh Singh; Dr. Kumar Shubhanshu (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Purpose: To compare external versus endoscopic dacryocystorhinostomy. Methods: In this prospective, randomized interventional study, total 100 patients (50 patients in each group) were enrolled as per exclusion and inclusion criteria for 1 year 6 months of study duration. Patients were randomized into two groups- Group I: 50 patients who were undergo external dacryocystorhinostomy (by one of the two surgeons) and Group II: 50 patients who were undergo endoscopic endonasal. Statistical analysis: It was performed using SPSS software (SPSS Inc., Chicago, IL, USA) for Windows program (21.0 version). Results: Among the both group majority of pt. were between 41-70 yr. In both the groups, females were predominant. The success rate of external DCR (98%) in this study was slightly higher than endoscopic DCR (94%) but was statistically non – significant. Conclusion: The difference between endoscopic and external DCR was not statistically significant. We concluded that these two distinct dacryocystorhinostomy methods are viable alternatives.